A Simple Strategy for Preparation of a Series of One-dimensional Rare Earth Oxides Using Rare Earth Precursors as Templates - Chen, Feng; Zhu, Ying-Jie; Wang, Ke-Wei; Pan, Yu-Bai (Current Nanoscience, 2009)
A simple route has been developed for the preparation of a series of one-dimensional rare earth (Y, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb) precursors by solvothermal treatment of corresponding rare earth nitrate in mixed solvents of N,Ndimethylformamide (DMF) and water at 200 °C without using any surfactant or additive. By a simple thermal transformation process, a series of rare earth oxides (Y2O3, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, and Yb2O3) with onedimensional structures have been obtained using corresponding one-dimensional rare earth precursor. The one-dimensional morphology of rare earth precursors can be well preserved and reproduced during the thermal transformation to corresponding rare earth oxides. This novel synthetic method also allows easy doping of rare earth ions into one-dimensional rare earth oxides examplified by Eu and Er doped yttrium oxide (Y2O3:Eu and Y2O3:Er). The photoluminescence properties of one-dimensional Y2O3:Eu and Y2O3:Er are investigated.
Keywords: one-dimensional